2019
DOI: 10.1038/s41598-019-40352-9
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of cold plasma-treated antibiotics and their antimicrobial activity

Abstract: Antibiotics, such as ofloxacin (OFX) and ciprofloxacin (CFX), are often detected in considerable concentrations in both wastewater effluents and surface water. This poses a risk to non-target organisms and to human health. The aim of this work was to study atmospheric cold plasma (ACP) degradation of antibiotics in water and meat effluent and to explore any residual antimicrobial activity of samples submitted to the plasma process. The results revealed that ACP successfully degraded the studied antibiotics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 80 publications
5
54
0
Order By: Relevance
“…However, the low removal efficiencies mentioned above may be explained by inadequate oxidant products for removing high concentrations of ofloxacin (41.23 mg/L) and amoxicillin (23.58 mg/L). e increase in the removal efficiency with an adequate increase in the applied voltage is consistent with the results reported by Sarangapani et al [21]; in their study, the authors have reported that with the rise in the voltage from 70 to 80 kV, the plasma degradation efficiency increased from 75% to 89% for ciprofloxacin and from 88% to 92% for ofloxacin. Even at an applied voltage of 35 kV, the highest removal efficiency was observed for ofloxacin and amoxicillin; however, the difference in removal efficiencies was not significant between the applied voltages of 30 kV and 35 kV.…”
Section: Effect Of Appliedsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the low removal efficiencies mentioned above may be explained by inadequate oxidant products for removing high concentrations of ofloxacin (41.23 mg/L) and amoxicillin (23.58 mg/L). e increase in the removal efficiency with an adequate increase in the applied voltage is consistent with the results reported by Sarangapani et al [21]; in their study, the authors have reported that with the rise in the voltage from 70 to 80 kV, the plasma degradation efficiency increased from 75% to 89% for ciprofloxacin and from 88% to 92% for ofloxacin. Even at an applied voltage of 35 kV, the highest removal efficiency was observed for ofloxacin and amoxicillin; however, the difference in removal efficiencies was not significant between the applied voltages of 30 kV and 35 kV.…”
Section: Effect Of Appliedsupporting
confidence: 90%
“…Recently, the application of cold plasma-one of the AOPs-has attracted considerable attention for wastewater treatment due to its efficiency, less chemical requirements, and low sludge production [17]. Cold plasma has been employed for the degradation of recalcitrant pollutants in the wastewater generated from pesticide production [18], a slaughterhouse [19], textiles [20], and pharmaceuticals [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species is generally identified as the main active species responsible for the effects of cold plasma, among which is degradation of chemical and biochemical compounds are atomic oxygen, ozone (O 3 ), hydrogen peroxides (H 2 O 2 ), hydroxyl radicals (•OH), as well as peroxynitrites and nitrogen oxides [23,24,41]. Some of the species, such as •OH, NO, O, after excitation emit in near UV-visual range and this emission is easily recordable by the optical emission spectroscopy (OES) technique.…”
Section: Optical Emission Spectroscopy and Electrical Characterizatiomentioning
confidence: 99%
“…Not long ago, the research focus of the plasma treatment was on its effects on pathogenic bacteria [21,22]. Lately, much attention has been paid to studies related to plasma effects on chemical and biological compounds which showed promising results [23][24][25]. Degradation of mycotoxins is being studied worldwide with different types of plasma sources.…”
Section: Introductionmentioning
confidence: 99%